PD-1/PD-L1 Inhibitor-Associated Myocarditis: Epidemiology, Characteristics, Diagnosis, Treatment, and Potential Mechanism - Dong, Hao; Qi, Yihang; Kong, Xiangyi; Wang, Zhongzhao; Fang, Yi; Wang, Jing (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) induce T-cell activation against cancer cells, and due to their anti-tumor function in multiple cancers, ICIs have been considered an important option for oncotherapy. PD-1/PD-L1 inhibitors are now widely used as ICIs for many types of cancers in clinical practices. Myocarditis induced by anti-PD-1/PD-L1 agents is uncommon but shows potentially fatal toxicity. In this review, we attempted to conclude the incidence, characteristics, diagnosis, and treatments, as well as illustrate the potential pathogenesis from the perspectives of T-lymphocyte infiltration, disturbance of regulatory T cells, cytokines, macrophage-mediated inflammatory response, and synergistic effect of PD-1/PD-L1 and CTLA4.